Pelatihan Penggunaan Aplikasi Geogebra bagi Siswa sebagai Sarana Pembelajaran Matematika : Pelatihan Penggunaan Aplikasi Geogebra bagi Siswa sebagai Sarana Pembelajaran Matematika - Hijriani, Lailin; Simarmata, Justin Eduardo; Nifu, Martha Marsella; Venidora Solo, Maria Fransiska (Kreativasi : Journal of Community Empowerment, 2025)
Every concept in mathematics is related to one another. In addition, a concept can be a prerequisite for another concept. Mastery of a concept is needed to learn other concepts. One of the materials that is an important foundation in mathematics is the linear equation. The material on linear equations is the basis for understanding more advanced mathematical concepts, such as geometry, statistics, and calculus. Therefore, a strong understanding of this material is very important for the junior high school level. Referring to information from subject teachers and students in the mathematics subject of linear equations for class VIII A, St. Aloysius Catholic Junior High School Niki-Niki explained that there are still many students in class VIII A who have learning outcomes that are below the criteria set by the school. So a solution is needed to solve the problems being experienced, one of which can be done is to carry out community service, namely providing training in the use of the Geogebra application which can significantly help students build an understanding of the concept of linear equations. Keywords : Instructional Media, Geogebra Application